ANALISIS FAKTOR-FAKTOR PENYEBAB PENURUNAN JUMLAH PENGUNJUNG DI TAMAN KYAI LANGGENG KOTA MAGELANG - Putri Ika Pertiwi; Ario Prima Sulka (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2026)
The decline in the number of visitors to Kyai Langgeng Park (TKL) in Magelang City in recent years has impacted regional income and the sustainability of economic activities in the surrounding community. This study aims to identify the factors causing the decline in visits and formulate an appropriate revitalization strategy for the management of Kyai Langgeng Park. The study used a qualitative descriptive approach supported by quantitative data on the number of visitors and ticket prices for the 2021–2025 period. Primary data were obtained through interviews, observations, and questionnaires with managers, visitors, traders, and MSMEs, while secondary data were taken from the DataGo website. The results showed that the decline in visits was influenced by internal factors such as the condition of the facilities that are starting to deteriorate, the lack of attraction innovation, inconsistent service quality, and a ticket price policy that is not commensurate with the value of the benefits received by visitors. External factors include competition with new destinations in the surrounding area, a shift in tourist behavior that prioritizes visual experiences and short tours, and weak digital promotion. The early ticket policy has proven effective in increasing visits, but is short-term. The study concluded that facility revitalization, attraction innovation, strengthening digital promotions, and adaptive pricing policies are key strategies to restore tourist interest and increase the attractiveness of Kyai Langgeng Park.